(3MGTjI Ydi TQM JdNjU GdeaJGMs - (3Ydj GdeWhds
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO agPg MhGT Ydi GdTQM GdeTghQ dJdNjU GdeaJGM cfJ bO jOJgG Ydjg s
(3BNQgG (B:s
(3Ydi eG ageg GdTGQM agh Ydi eG JQi ai GdQcGcI hGdaSGO s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GddZIs